Flame‐Engraved Nickel–Iron Layered Double Hydroxide Nanosheets for Boosting Oxygen Evolution Reactivity. Issue 7 (17th May 2018) - Zhou, Daojin; Xiong, Xuya; Cai, Zhao; Han, Nana; Jia, Yin; Xie, Qixian; Duan, Xinxuan; Xie, Tianhui; Zheng, Xiaolin; Sun, Xiaoming; Duan, Xue
Abstract: Introducing oxygen vacancies to metal oxide materials would improve their catalytic activity but usually needs reductive reagents (e.g., H2 ) and high temperatures (e.g., >600 °C), which is unsafe, complex, and time consuming. Herein, a fast (30 s) and facile (operated at ambient conditions) flame‐engraved method is used to introduce abundant oxygen vacancies and well‐defined hexagonal cavities with (110) edges to nickel–iron layered double hydroxides (NiFe‐LDH). Abundant oxygen vacancies, lower coordination numbers, and electron‐rich structures of Ni and Fe sites emerge in the flame‐engraved NiFe‐LDH array electrode, leading to its onset potential as low as 1.40 V (vs reversible hydrogen electrode) for oxygen evolution reaction. This highlights the importance and convenience of flame‐engraving method in preparing metal hydroxides with abundant oxygen vacancies, which can be used as efficient electrochemical catalysts. Abstract : Abundant oxygen vacancies are introduced to a NiFe‐layered double hydroxide array by a fast reducing flame treatment of 30 s, which operates in an open environment. The formation of oxygen vacancies, dangling bonds, and electron‐rich structure of metal sites in flame engraves nickel–iron layered double hydroxides (NiFe‐LDH), which contribute to the 1.40 V oxygen evolution onset potential and fast current density increasement.